Systemic implications of transatlantic regulatory cooperation and competition - Evenett, Simon J.; Stern, Robert M. (Robert Mitchell), 1927-2015 (World Scientific studies in international economics, 2011)
Regulations and enforcement decisions that at first appear to have only a domestic impact can have substantial spillover effects on other nations' economies. Experience has shown time and again that there is no reason to expect that these effects are confined to jurisdictions at the same level of development. Governments on both sides of the Atlantic recognize this, yet their responses in many policy areas are not aligned - sometimes deliberately so. This creates a complex regulatory landscape that appears to be the product of both cooperation and competition, and which can only be fully under.